2021
DOI: 10.3390/biomedicines9111570
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Schedule of PARP Inhibitors in Combination with 177Lu-DOTATATE: A Dosimetry Rationale

Abstract: 177Lu-DOTATATE for neuroendocrine tumours is considered a low-toxicity treatment and may therefore be combined with other pharmaceuticals to potentiate its efficacy. One approach is to add a poly-[ADP-ribose]-polymerase (PARP) inhibitor to decrease the ability of tumour cells to repair 177Lu-induced DNA damage. To decrease the risk of side effects, the sequencing should be optimized according to the tumour-to-normal tissue enhanced dose ratio (TNED). The aim of this study was to investigate how to enhance 177L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Independent from HRD, the combination of PRRT and PARPi seems to be an interesting option to induce synthetic lethality and to enhance treatment efficacy. A study tried to optimize the treatment combination of PRRT and PARPi [ 14 ]. Two phase-1 studies PARLuNET for NET G2 (NCT05053854) and LuPARP for NET G2/G3 (NCT04375267) are ongoing to evaluate the feasibility and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Independent from HRD, the combination of PRRT and PARPi seems to be an interesting option to induce synthetic lethality and to enhance treatment efficacy. A study tried to optimize the treatment combination of PRRT and PARPi [ 14 ]. Two phase-1 studies PARLuNET for NET G2 (NCT05053854) and LuPARP for NET G2/G3 (NCT04375267) are ongoing to evaluate the feasibility and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the full radiosensitizing potential of olaparib is likely to be achieved using distinct schedules and doses. For 177 Lu-DOTATATE, a dosimetry-based schedule rationale is to start the PARP inhibitor 24 h after the infusion of 177 Lu-DOTATATATE and continue for 4 weeks at each cycle [ 8 ]. As for EBRT, Verhagen et al suggested that a short 7 h exposure (1 h before and 6 h after irradiation) of the PARP inhibitor is sufficient for radiosensitization [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such data are needed to fully exploit RNT potential, including in the context of treatment combination strategies. For example, DNA repair targeting strategies (i.e., using poly (ADP-ribose) polymerase (PARP) inhibitors) have shown promise in combination with EBRT and were therefore also tested in combination with RNT; however, different radiobiological considerations may need to be applied for efficient radiosensitization [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combining TRT with potentially synergistic agents (chemotherapy, immune checkpoint inhibitors, PARP inhibitors, etc.) or with other radiopharmaceuticals is being evaluated in ongoing clinical trials (14)(15)(16)(17). The focus of this paper is to describe and explore a novel technology platform that may improve the therapeutic effect of TRT by combining two radionuclides from the same decay chain; one TAT component targeting the stromal elements of osteoblastic skeletal metastases and the other by selective cell-surface binding to cancer cells in extraskeletal and skeletal metastases.…”
Section: Introductionmentioning
confidence: 99%